Structural safety assessment of geometrically complex masonry vaults by non-linear analysis. The Chapel of the Würzburg Residence (Germany). (1st June 2017) - Compán, Víctor; Pachón, Pablo; Cámara, Margarita; Lourenço, Paulo B.; Sáez, Andrés
Highlights: Geometrically complex brick masonry vaults have been analysed to assess their structural safety. Operational Modal Analysis technique is used to dynamically characterise masonry vaults. Genetic algorithms are used for numerical models updating. Updated FE model is used to perform a nonlinear analysis. Abstract: This paper addresses the structural safety assessment of the Chapel of the Würzburg Residence (Germany), one of the most important churches of the Central European Baroque. It was declared as World Heritage Site by UNESCO in 1981, one of its most unique and distinctive characteristics is the geometry of its complex vaults. Intersections between vaults are warped and vaults surfaces were built using only one layer of brick masonry. In this work, a nonlinear finite elements (FE) model has been developed and used to assess the structural safety of the building. In order to update the model by identifying the dynamic response of the building, experimental ambient vibration tests have been previously subsequently carried out. Operational Modal Analysis (OMA) has been used to experimentally identify both modal displacements and natural frequencies. The numerical FE model is them adjusted using genetic algorithms until its dynamic response resembles that experimentally observed, thus providing a valid model to further analyse the structural behaviour of the building. After briefly descripting the Chapel, the methodology followed to update the numerical model and the obtained results from a non-linear analysis on this over-complex vaulted structure are the main goals of the paper.